What Happens When Investigating A Crime Takes Up Too Much Time? An Examination of How Optimal Law Enforcement Theory Impacts Sentencing - Ray, Katherine; L. Borkowski, Elizabeth; Leal, Wanda; D. Bales, William (International Journal of Criminology and Sociology, 2017)
Previous research finds that variations in sentencing outcomes still exist among similarly situated individuals, especially among drug offenders. While courtroom actors are often the focus of sentencing disparities, law enforcement officers are rarely studied. This is problematic because criminological research has yet to explore whether law enforcement could influence sentencing decisions. The current study aims to discover the influence of a previously ignored legal variable, investigation workload, on sentence length and directly examine an untested criminal justice theory, Optimal Law Enforcement Theory. This study will explore these overlooked concepts with a rare dataset that contains information on individuals convicted of prescription drug trafficking in Florida from 2011-2013. We find that investigation workload does influence sentencing, with offenders convicted from a high police workload being significantly more likely to experience longer sentences than offenders convicted from a low investigation workload. Limitations and policy implications are also discussed.